Widening inequality: Diverging trends in CO2 and air pollutant emissions across Chinese cities - Shuangzhi Li; Xiaoling Zhang; Zhongci Deng; Kang Liu; Jing Wang; Jin Fan (Resources, Environment and Sustainability)
Chinese cities face escalating tensions between pollution mitigation and economic equity. Using an environmentally extended multi-regional input–output (EE-MRIO) model, we quantified the carbon and air pollutant footprints of 309 cities from 2012 to 2017 and applied structural decomposition analysis (SDA) to identify key emission drivers. The results indicate that inequality in air pollutant emissions, with a Gini coefficient of 0.31–0.53, is significantly higher than that of CO2 (0.33–0.41). Developed cities generate 3.1 times more economic output per unit of CO2 emissions than less developed cities, with the disparity widening over time. While intermediate input optimization contributed to a 1.94 Gt reduction in CO2 emissions, its benefits were largely concentrated in developed regions and were accompanied by increased emissions of PM2.5, BC, OC, and CO. Although reductions in emission intensity played a crucial role in mitigating pollutants, they paradoxically contributed to CO2 growth in energy-intensive cities. Additionally, population growth and per capita final demand were the primary drivers of emission increases, and population growth had a greater impact on developed regions. These findings underscore the need for regionally differentiated policies, including carbon quota reallocation, industrial transformation in energy-dependent cities, and the promotion of green industries in less developed areas, to achieve a balance between environmental sustainability and economic development.